Национальные и этнические меньшинства в Польше в свете переписи населения 2002 года - Бабиньский, Г. (Социология: теория, методы, маркетинг, 2005)
The following article attempts to analyze and interpret the findings of the National Census 2002 with respect to national and ethnic minorities. Apart from a concise summary of numerical data from particular voivodships, much attention is paid to such issues as: methodological remarks regarding questions about the respondents’ national identity entailed in the census and the effects of asking such questions, factors distorting one’s declaration of national identity, some comments and reactions of minorities to the census results. I hold a more analytic approach towards the three biggest minorities: German, Ukrainian and Belarussian. The census results provide many important data but only when we treat them as complementary information and also when the numbers are somehow considered relative to the situation of a particular minority, as well as the direction and stage of the situation’s change. Thanks to the census we know much more about national and ethnic minorities in Poland. This knowledge is, however, secondary, partial, allowing more for formulating hypotheses than firm conclusions. For example we know for sure that there exists a Silesian identification functioning as a basic ethnic identity, which cannot be narrowed to regional one. However, we do not know much about the further evolution of this community.